2021
DOI: 10.1007/s00394-020-02449-0
|View full text |Cite
|
Sign up to set email alerts
|

Fruit intake, genetic risk and type 2 diabetes: a population-based gene–diet interaction analysis

Abstract: Purpose Whether the association between fruit and type 2 diabetes (T2D) is modified by the genetic predisposition of T2D was yet elucidated. The current study is meant to examine the gene–dietary fruit intake interactions in the risk of T2D and related glycemic traits. Methods We performed a cross-sectional study in 11,657 participants aged ≥ 40 years from a community-based population in Shanghai, China. Fruit intake information was collected by a validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…There is interest in identifying genetic loci implicated in fasting glucose and lifestyle-gene interactions that modify the incidence of T2D because they may suggest relevant biological pathways [ 26 , 27 ]. Interaction between fruit intake and polygenic genetic risk for type 2 diabetes have shown an effect on both diabetes risk and on fasting glucose [ 28 ]. Similar studies have explored interaction with SSB, without conclusive results [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is interest in identifying genetic loci implicated in fasting glucose and lifestyle-gene interactions that modify the incidence of T2D because they may suggest relevant biological pathways [ 26 , 27 ]. Interaction between fruit intake and polygenic genetic risk for type 2 diabetes have shown an effect on both diabetes risk and on fasting glucose [ 28 ]. Similar studies have explored interaction with SSB, without conclusive results [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the association directions between asthma and six factors (BMI, insomnia, MET score, neuroticism score, time spent watching TV, and TDI) correspond to the findings of previous studies ( Hedlund et al, 2006 ; Eijkemans et al, 2012 ; Meltzer et al, 2014 ; Vancampfort et al, 2017 ; Kavanagh et al, 2018 ; Najjab et al, 2020 ), suggesting reasonably acceptable associations. Several studies have used disease outcomes from a cross-sectional dataset for interaction analysis and derived important results ( Eze et al, 2016 ; Jia et al, 2021 ). Next, some environmental data in the present study are from self-reported questionnaires (e.g., alcohol intake frequency, insomnia, MET score, neuroticism score, time spent watching TV, and TDI) that are prone to responder bias ( Rask-Andersen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A semistructured questionnaire collected information on demographic and socioeconomic characteristics, medication usage, activity, food frequency, and so on. Compared with the traditional dietary records, food frequency information was collected by asking the frequency of intake for particular food items (e.g., meat, vegetables, fruit, and so on) over the past year . Body mass index (BMI) was computed as body weight (kg)/height 2 (m 2 ).…”
Section: Methodsmentioning
confidence: 99%